Ultralong thermally activated delayed fluorescence based on intermolecular charge transfer induced by isomer in carbazole derivative - Junru Chen; Xianhe Zhang; Zongliang Xie; Bin Liu (Aggregate)
Abstract Ultralong thermally activated delayed fluorescence (UTADF) materials play an important role in realizing time‐dependent color‐tunable afterglow. Some typical carbazole (Cz) derivatives have been reported to exhibit UTADF properties. However, a 10‐fold difference in TADF lifetime was found between commercial Cz derivatives and the corresponding lab‐synthesized ones, which indicated that UTADF may not be derived from the single Cz derivatives as reported. To reveal the real mechanism, we synthesized three Cz derivatives and one isomer to form three host‐guest pairs for optical studies. The photophysical properties revealed that UTADF originated from the intermolecular charge transfer between host and guest, while the ultralong organic phosphorescence was from the guest. Thanks to the rich color variations in luminescence displayed by 4‐(1H‐benzo[f]indol‐1‐yl)−4′‐(9H‐carbazol‐9‐yl)‐[1,1′‐biphenyl]−3,3′‐dicarbonitrile/4,4′‐di(9H‐carbazol‐9‐yl)‐[1,1′‐biphenyl]−3,3′‐dicarbonitrile (CBP‐2CN) at different delay times, it can be applied to realize multi‐dimensional encryption in both delay time and luminescent color.